Nollywood movies watching pattern and risky sexual behaviour among in-school adolescents in selected South-Western Nigeria secondary schools (2020)
Nollywood movies are being released at exponential rates. With an average of 50 movies being released on a weekly basis. Observations have revealed that a number of the films produced, and which are accessible to in-school adolescents promotes risky sexual behaviour. In-school adolescents are in their formative years and access to these types of films can affect their sexual behaviour. This study surveyed the Nollywood movies watching pattern and risky sexual behaviour among in-school adolescents. A correlational survey was carried out using the quantitative method. A total of 644 students were sampled using the probability proportionate to size sampling technique while a pre-tested questionnaire with reliability coefficient of 0.75 (r = 0.75) was used as data gathering instrument. Data were analysed using the descriptive method of frequency counts, percentages, mean and standard deviation for objectives 1 and 2 while Pearson Product Moment Correlation (PPMC) was used for objective 3. Result showed that majority of the in-school adolescents surveyed have access to Nollywood movies with sexual content (60.0%), though their parents censors the movies (63.8%). Correlation was found between Nollywood watching pattern and risky sexual behaviour among in-school adolescents in selected south-western Nigeria secondary schools (r = .266**, N= 644, p<.05). The study therefore, recommended that parents should continue to censor movies watched by their wards.